Potential contribution of agronomic practices and conservation agriculture towards narrowing smallholders' yield gaps in Southern Africa: Lessons from the field - Nyagumbo, Isaiah; Nyamayevu, Donald; Chipindu, Lovemore; Siyeni, Donald; Dias, Domingos; Silva, João Vasco (Cambridge University Press, 2024)
Smallholders in Southern Africa continue to grapple with low maize productivity despite this being the staple food crop. This study sought to analyze and isolate the relative contribution of agronomic practices to maize yields obtained by smallholders in Malawi and Mozambique using data generated from on-farm trials testing the performance of conservation agriculture cropping systems. The trials were implemented in two communities, namely Kasungu district in Malawi and Sussundenga district in Mozambique, and ran for seven consecutive growing seasons starting in 2010-2011. Maize yield was measured annually in the on-farm trials, which included a 'control treatment' representing an improved farm practice, and in neighboring fields managed by the same farmers on their own, hence representing a 'true farm practice'. Results indicated that maize yield increased linearly with increasing plant population at harvest at both sites. On average, an increase in plant population at harvest by 1000 plants ha-1 resulted in an increase in maize yield of 90 and 63 kg ha-1 at Kasungu and Sussundenga, respectively. The greatest maize yields were obtained when plant population at harvest exceeded 40 000 plants ha-1. Yet, the plant population at harvest was below the generally recommended optimum for most of the cropping systems studied and in most growing seasons. Furthermore, the use of agronomic practices alone without conservation agriculture (i.e., improved varieties, fertilizer management, and timely weed control) resulted in maize yield gains of as much as 54% and 43% relative to the 'true farm practice' at Kasungu and Sussundenga, respectively. Overall, the proportion of these yield increases relative to the 'true farm practice' accounted for by agronomic practices amounted to 53-70% and 57-85% at Kasungu and Sussundenga for the highest to the lowest-yielding cropping system. Although conservation agriculture significantly improved maize yield at both sites, such increases were smaller in magnitude compared to the yield gains derived from improved agronomic practices. The study suggests that considerable strides toward narrowing maize yield gaps in Southern Africa can be achieved through improvement of current crop management practices, let alone adhering to the conservation agriculture principles of minimum tillage, residue retention, and crop diversification.